Tantangan Masyarakat dalam Menjaga Persatuan dan Kesatuan di Tahun Politik - Duwi Handoko; Beni Sukri; Hulaimi; Khairul Azwar Anas; Lewiaro Laia; Meidizon (JURNAL SOSIO-KOMUNIKA, 2023)
National unity and integrity are crucial for political stability and security in Indonesia. However, during political campaigns, differences in political views and interests often lead to conflicts that can threaten national unity and integrity. This challenge is becoming more complex in the digital era and social media, where information can easily spread and reinforce polarization. Therefore, this research aims to examine the challenges of maintaining national unity and integrity in Indonesia amidst differences in political views and interests during political campaigns and efforts that can be made by the community and the government to overcome these challenges. This research is a normative legal research. The data collection method used is a literature study by reviewing literature related to the research object. Data analysis is carried out systematically based on the research problem formulation and described qualitatively. The challenges faced by society in maintaining national unity and integrity in the political year are framing narratives that reinforce polarization, spreading false information or hoaxes, using hate speech, and using identity politics. Efforts need to be made to overcome these challenges, such as increasing digital and media literacy, developing a better understanding of human rights and equality, and promoting constructive and inclusive dialogues between different social groups. Active involvement from all parties, including the government, society, and media, is also crucial in maintaining national unity and integrity during political campaigns.